Integrating Pt nanoparticles with 3D Cu2-xSe/GO nanostructure to achieve nir-enhanced peroxidizing Nano-enzymes for dynamic monitoring the level of H2O2 during the inflammation - Shen, Man; Dai, Xianling; Ning, Dongni; Xu, Hanqing; Zhou, Yang; Chen, Gangan; Ren, Zhangyin; Chen, Ming; Gao, Mingxuan; Bao, Jing (Frontiers in Immunology, 2024)
The treatment of wound inflammation is intricately linked to the concentration of reactive oxygen species (ROS) in the wound microenvironment. Among these ROS, H2O2 serves as a critical signaling molecule and second messenger, necessitating the urgent need for its rapid real-time quantitative detection, as well as effective clearance, in the pursuit of effective wound inflammation treatment. Here, we exploited a sophisticated 3D Cu2-xSe/GO nanostructure-based nanonzymatic H2O2 electrochemical sensor, which is further decorated with evenly distributed Pt nanoparticles (Pt NPs) through electrodeposition. The obtained Cu2-xSe/GO@Pt/SPCE sensing electrode possesses a remarkable increase in specific surface derived from the three-dimensional surface constructed by GO nanosheets. Moreover, the localized surface plasma effect of the Cu2-xSe nanospheres enhances the separation of photogenerated electron-hole pairs between the interface of the Cu2-xSe NPs and the Pt NPs. This innovation enables near-infrared light-enhanced catalysis, significantly reducing the detection limit of the Cu2-xSe/GO@Pt/SPCE sensing electrode for H2O2 (from 1.45 μM to 0.53μM) under NIR light. Furthermore, this biosensor electrode enables in-situ real-time monitoring of H2O2 released by cells. The NIR-enhanced Cu2-xSe/GO@Pt/SPCE sensing electrode provide a simple-yet-effective method to achieve a detection of ROS ( H2O2、-OH) with high sensitivity and efficiency. This innovation promises to revolutionize the field of wound inflammation treatment by providing clinicians with a powerful tool for accurate and rapid assessment of ROS levels, ultimately leading to improved patient outcomes.